Outcomes of using telehealth for the provision of healthcare to Aboriginal and Torres Strait Islander people: a systematic review - Liam J. Caffery; Natalie K. Bradford; Sumudu I. Wickramasinghe; Noel Hayman; Anthony C. Smith (Elsevier, 2017)
Abstract Objective: To examine reported outcomes of health services delivered by telehealth to Indigenous Australians. Methods: Systematic review of the literature. Searches were conducted to identify articles that reported a telehealth service used to provide clinical services to Indigenous Australians. Articles were screened for inclusion using pre‐defined criteria. Findings were synthesised narratively and reported using the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) guidelines. Results: 14 articles, describing 11 distinct telehealth services, were selected based on the inclusion criteria. Authors of included studies report that telehealth has improved social and emotional wellbeing, clinical outcomes and access to health services for Indigenous Australians. Further, it has reduced travel and improved screening rates. Indigenous people report positive perceptions of their telehealth interaction. Conclusion: Telehealth is used to address poor accessibility to health services and for targeted screening programs for at risk populations. Reported outcomes from existing services demonstrate the potential of telehealth for health service delivery for Indigenous Australians. Confidence in the findings of this review is reduced by the predominance of descriptive studies and small sample sizes in many of the included articles. Implications: Telehealth models of care facilitated through partnerships between Aboriginal community‐controlled health services and public hospitals may improve both patient outcomes and access to specialist services for Indigenous people.